2019
DOI: 10.1073/pnas.1908176117
|View full text |Cite
|
Sign up to set email alerts
|

Descending projections from the substantia nigra pars reticulata differentially control seizures

Abstract: Three decades of studies have shown that inhibition of thesubstantia nigra pars reticulata(SNpr) attenuates seizures, yet the circuits mediating this effect remain obscure. SNpr projects to the deep and intermediate layers of the superior colliculus (DLSC) and the pedunculopontine nucleus (PPN), but the contributions of these projections are unknown. To address this gap, we optogenetically silenced cell bodies within SNpr, nigrotectal terminals within DLSC, and nigrotegmental terminals within PPN. Inhibition o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 74 publications
(90 reference statements)
0
30
0
Order By: Relevance
“…We had hypothesized that the DLSC might be a critical site of action for CB-mediated anti-convulsant effects. This was based on: (1) the well-established role the DLSC plays in audiogenic seizures, and in particular, in the wild-running phase which is typical of the GEPR-3 strain (Merrill et al, 2005 ); (2) volumetric changes in the SC in GEPR-3 rats (Lee et al, 2018 ); (3) the interconnections between the substantia nigra pars reticulata and the DLSC and the density of CB1 receptors in the SNpr (Herkenham et al, 1991 ; Matsuda et al, 1992 ; Glass et al, 1997 ; Tsou et al, 1998 ); (4) the presence of CB1 immunopositive axons in the DLSC (Tsou et al, 1998 ; Sañudo-Peña et al, 2000 ); (5) the anticonvulsant effects of activation of the DLSC (Soper et al, 2016 ); and (6) the anticonvulsant effects of disinhibition of the SC through inhibition of nigrotectal projections (Wicker et al, 2019 ). Consistent with our hypothesis, we found that the focal application of CP to the DLSC suppressed both AGSs and AT-evoked seizures.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We had hypothesized that the DLSC might be a critical site of action for CB-mediated anti-convulsant effects. This was based on: (1) the well-established role the DLSC plays in audiogenic seizures, and in particular, in the wild-running phase which is typical of the GEPR-3 strain (Merrill et al, 2005 ); (2) volumetric changes in the SC in GEPR-3 rats (Lee et al, 2018 ); (3) the interconnections between the substantia nigra pars reticulata and the DLSC and the density of CB1 receptors in the SNpr (Herkenham et al, 1991 ; Matsuda et al, 1992 ; Glass et al, 1997 ; Tsou et al, 1998 ); (4) the presence of CB1 immunopositive axons in the DLSC (Tsou et al, 1998 ; Sañudo-Peña et al, 2000 ); (5) the anticonvulsant effects of activation of the DLSC (Soper et al, 2016 ); and (6) the anticonvulsant effects of disinhibition of the SC through inhibition of nigrotectal projections (Wicker et al, 2019 ). Consistent with our hypothesis, we found that the focal application of CP to the DLSC suppressed both AGSs and AT-evoked seizures.…”
Section: Discussionmentioning
confidence: 99%
“…These drug doses were chosen based on published reports (Sañudo-Peña et al, 2000 ; Citraro et al, 2013 ; Florek-Luszczki et al, 2014a ). Drug microinfusions were performed essentially as we have previously described (Wicker and Forcelli, 2016 ; Wicker et al, 2019 ). In brief, rats were gently restrained and a 28-gauge internal cannula was inserted.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Unilateral optogenetic stimulation also suppressed seizures but was accompanied by behavioral adverse effects such as contraversive posturing, freezing, or startle response in some of the rats. Optogenetic inhibition of SNr cells suppressed generalized seizures evoked by PTZ, focal bicuculline-induced seizures evoked from the anterior piriform cortex, absence seizures evoked by gamma-butyrolactone, and audiogenic seizures in genetically epilepsy-prone rats [248]. Noteworthy, these effects were reproduced by silencing nigrotectal projections, while silencing nigrotegmental terminals reduced only absence seizures and exacerbated seizures evoked by PTZ, showing that specific efferent projection pathways differentially control different seizure types [248].…”
Section: Further Regionsmentioning
confidence: 99%